Migrant health research in the Republic of Ireland: a scoping review - Nazmy Villarroel; Ailish Hannigan; Santino Severoni; Soorej Puthoopparambil; Anne MacFarlane (BMC, 2019)
Abstract Background Migration to European countries has increased in number and diversity in recent years. Factors such as access to healthcare, language barriers and legal status can impact the health outcomes of migrant groups. However, little is known about the evidence base on the health status of migrants in the Republic of Ireland. Our aim was to scope existing peer-reviewed research on the health of migrants in Ireland and identify any gaps in the evidence. Methods We conducted a scoping review of peer-reviewed research on the health of migrants in the Republic of Ireland. Eleven electronic databases were searched for peer-reviewed, empirical articles published between 2001 and 2017. Search terms were adapted from a World Health Organisation review. Findings were analysed using the 2016 World Health Organisation Strategy and Action Plan for Refugee and Migrant Health in the World Health Organisation European region, which outlines nine strategic areas that require collaborative action. Results Of 9396 articles retrieved, 80 met inclusion criteria, with the majority (81%) published since 2009. More than half of the studies had a quantitative design (65%). Migrants studied came from Eastern Europe, Asia and Africa and included labour migrants, refugees and asylum seekers. Most studies related to two World Health Organisation strategic areas; 4: "achieving public health preparedness and ensuring an effective response", and 5: "strengthening health systems and their resilience". Conclusion There is growing attention to migrant health in Ireland with a balance of qualitative and quantitative research. While much of the identified research is relevant to three of the World Health Organisation strategic areas, there are significant gaps in the other six areas. The study design could be replicated in other countries to examine and inform migrant health research.